Neisseria meningitidis serogroup B causing invasive disease, Italy, 2010–2021 - Paola Vacca; Fenicia Vescio; Fortunato D’Ancona; Cecilia Fazio; Arianna Neri; Anna Carannante; Luigina Ambrosio; Florigio Romano Lista; Silvia Fillo; Andrea Ciammaruconi; Antonella Fortunato; Paola Stefanelli (PLoS ONE, 2025)
In Italy, Invasive Meningococcal Disease (IMD) due to Neisseria meningitidis serogroup B (MenB) showed the highest incidence rates in infants under one year of age. This study describes the main characteristics of MenB responsible for invasive diseases circulating in Italy from 2010 to 2021. Data collected within the framework of National Surveillance System (NSS) for IMD were analysed. Serogroup confirmed IMD cases were included in the study. For unspecified meningococcal serogroup, a multinomial model was used to impute the serogroup. Antimicrobial susceptibility and genotyping by Sanger or whole genome sequencing were performed on viable meningococci. Core genome MLST (cgMLST) was evaluated using a gene-by-gene approach, and MenDeVAR analyses were used to assess potential coverage by MenB vaccines. A total of 1845 IMD cases were reported to the NSS, of which 704 were laboratory confirmed as MenB and another 232 were statistically attributed to this serogroup. The highest incidence rate for IMD due to MenB was observed in infants <1 year, followed by children aged 1–4 years. MenB isolates were susceptible to antimicrobials except for 4 isolates, of which 2 resistant to penicillin G, 1 to rifampicin and 1 to ciprofloxacin. High genetic variability was observed, with clonal complex (cc) cc41/44 being replaced by the cc162 since 2015. MenDeVAR analyses highlighted a high proportion of genomes classified as “insufficient data,” especially among recent isolates. Despite the low incidence of IMD in Italy, MenB increased in specific age groups during the study period. Continuous genomic surveillance, including MenDeVAR monitoring, remains essential to detect changes in circulating MenB and predict vaccine coverage.